1984
DOI: 10.1159/000287820
|View full text |Cite
|
Sign up to set email alerts
|

What the Future Holds for Psychosomatic Medicine

Abstract: In the recent past, the questions that face a comprehensive psychosomatic medicine have been defined. These questions refer to the context in which disease begins, the timing of the onset of the disease, the role of previous social experience in predisposing to disease, and the choice of the particular disease. It is suggested that a study of bereavement may be paradigmatic in answering these four questions: Bereavement has been cited as a factor in a large variety of disease. However, bereavement may produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This means that for a given amount of energy required to sustain basal cellular functions, Dex-treated fibroblasts maintained an even larger spare J ATP-OxPhos capacity than control cells – an effect that persisted across the lifespan (p < 0.0001, Fig. 3D ) and consistent with the anticipatory process of allostasis and allostatic load ( McEwen, 1998 ; McEwen and Stellar, 1993 ; Sterling and Eyer, 1988 ; Weiner and Mayer, 1990 ).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…This means that for a given amount of energy required to sustain basal cellular functions, Dex-treated fibroblasts maintained an even larger spare J ATP-OxPhos capacity than control cells – an effect that persisted across the lifespan (p < 0.0001, Fig. 3D ) and consistent with the anticipatory process of allostasis and allostatic load ( McEwen, 1998 ; McEwen and Stellar, 1993 ; Sterling and Eyer, 1988 ; Weiner and Mayer, 1990 ).…”
Section: Resultsmentioning
confidence: 55%
“…In response to environmental stressors, living organisms mount evolutionarily conserved responses that aim to increase resilience and promote survival, a phenomenon termed allostasis ( Sterling and Eyer, 1988 ; Weiner and Mayer, 1990 ). However, the chronic activation of these responses produces allostatic load ( McEwen and Stellar, 1993 ; McEwen, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated by studies reported by Vein, transformation of neuromental tension (stress) into somatic illness is mediated via the autonomic nervous system, a view which has been supported by Marilov's studies of psychosomatoses [13]. The physiological and neurophysiological mechanisms of this transformation have thus far received insuffi cient study and this aspect requires further development [20].…”
mentioning
confidence: 99%